Poesie - Musik - Übersetzung Varietäten in der Translation von Liedtexten - Kvam, Sigmund (TRANSÜD. Arbeiten zur Theorie und Praxis des Übersetzens und Dolmetschens, 2024)
The translation of art songs is an attractive subject of research: their musical aesthetics unite two "sacred originals" - the poetry of a renowned poet's text and the melody of a respected composer. In view of the long tradition of art song in the German-speaking world, the use of German in translation practice is of particular interest. Sigmund Kvam has examined German translations of Norwegian and Danish art songs by the composer Edvard Grieg. On the basis of functional translation theory, he specifies the characteristics of this particular translation context and demonstrates the special use of linguistic rules in the translation process, focusing on text linguistics, syntax, topology, morphology and lexis. His findings are just as fruitful for linguistics and translation studies as they are for singers. The possible consequences for the singability of translated art songs are particularly relevant here.